Enhancing the Usefulness of Blockchain Technology in Finance Sector - Vedran Juričić; Matea Radošević; Ena Fuzul (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 12-14 September 2019, 2019)
Blockchain technology has become widely popular with the appearance of cryptocurrencies that use the decentralized nature of blockchain in order to exchange funds between their users. In order to verify various needed details during an exchange, consensus mechanisms are used which solve simple but exhaustive calculations. Such operations fulfil their primary goal of verifying, but are a common target of public disapproval due to massive energy consumption and lack of usefulness. This work discusses different approaches and consensus mechanisms with a more useful secondary function, especially focusing on NP-complete problems as mediators in solving complex and resource-heavy problems. A new way of approaching these problems can benefit many areas, like science, healthcare, government and finance, optimizing the current infrastructure and business processes like markets, transactions, insurances, payments and supply chains, or creating more secure, reliable and efficient environment.
Keywords: C61; 330; blockchain; proof of work; optimization; problem solving